Modernisation of Higher Education in the Context of European Integration ? A Comparative Analysis - Gheorghe Epuran; Iuliana Petronela Gârdan; Daniel Adrian Gârdan; Bianca Tescasiu (Amfiteatru Economic)
Modernization of higher education system is a complex process and it became a priority on the agenda of the concerns of both European Union and each Member States levels. In this article we present the results of the analysis of the main aspects of the modernization of higher education system of Romania after its integration in European Union, compared to the evolution of other Member States, in the same period, from the perspective of three indicators: access, retention and employability. In order to achieve the proposed objective, we conducted a research and an aggregation of data from secondary available sources, reports of the European Commission and various statistical reports which will be referred to throughout the article.